Laboratory diagnosis of malaria infection - A short review of methods - Chotivanich, K; Silamut, K; Day, N (2006)
Malaria is one of the most important tropical infectious diseases. The incidence of malaria worldwide is estimated to be 300-500 million clinical cases each year with a mortality of between one and three million people worldwide annually. The accurate and timely diagnosis of malaria infection is essential if severe complications and mortality are to be reduced by early specific antimalarial treatment. This review details the methods for the laboratory diagnosis of malaria infection.